Art and Science: The medicinal plants in Codex Martínez Compañón - Victorio Cánovas, Emma Patricia (2021)
Since its discovery, a series of papers have recognized the importance of the painted watercolors ordered by Bishop Baltasar Jaime Martínez Compañón y Bujanda to show his diocese areas and general characteristics. Completing this task was entrusted to a group of anonymous and self-taught artists who used the available resources at their disposal. The resulting works aren’t usually considered study objects by art history. This article reviews the botanical illustrations in the codex, focuses on medicinal use plants and their recognition not only as a visual resource at the service of science but also as artistic works.